Non-verbal nurse-parturient communication in labor in Portuguese-speaking countries - Gilmara de Lucena Beserra; Paula Marciana Pinheiro de Oliveira; Lorita Marlena Freitag Pagliuca; Paulo César de Almeida; Saiwori de Jesus Silva Bezerra dos Anjos; Ana Karina Bezerra Pinheiro
Objective: to analyze nonverbal communication between nurse and parturient during the active phase of labor in two Portuguese-speaking countries. Method: a quantitative and analytical study, whose sample consisted of 709 interactions that used the nonverbal communication of nurses and parturients. The analyzed variables were: distance; posture; axis; contact; emblematic gestures; illustrator gestures and regulatory gestures. For the analysis of the data, the Chi-Square and Likelihood Ratio tests were used. Results: the intimate distance between nurse and parturient in both countries (p = 0.005) prevailed. In both, touch was the most commonly used form of contact (p <0.0001). In both countries, the parturient remained lying down (p <0.0001). In relation to the established contact (p <0.0001), the parturient did not use contact. The face-to-face axis predominated in the interactions in both countries between nurse-parturient (p <0.0001) and parturient-nurse (p <0.0001). Conclusion: similarities were observed in non-verbal communication between nurses and parturients in both countries. However, there are differences such as the established contact between Brazilian and Cape Verdean nurses to parturients.